How Rational Is the Response of Individuals to the Threat of Terrorism in Europe? - Olaf J. de Groot; Konstantinos Drakos; Cathérine Müller (Deutsches Institut für Wirtschaftsforschung (DIW), 2011)
In this Policy Briefing, we address two important questions. We look at the drivers of concern about terrorism and find that beyond individual characteristics, it is also affected by the occurrence of terrorism. When distinguishing between permanent and transitory terrorism, the first has a much stronger impact than the first. The second question concerns how terrorism affects the policy preferences of voters. We find that while a higher level of terrorist concern does increase people's willingness to trade off civil liberties for more security, a singular attack has only a temporary effect. After only a few months, people's preferences return towards their pre-attack levels.
info:eu-repo/grantAgreement/EC/FP7/218105
Keywords: 330